‘DAMNATIO AD BESTIAS’ – RODZAJ KARY ŚMIERCI CZY SPOSÓB JEJ WYKONANIA? - Kubiak, Przemysław (Zeszyty Prawnicze, 2016)
‘DAMNATIO AD BESTIAS’ – KIND OF DEATH PENALTY OR MODE OF EXECUTION? Summary Damnatio ad bestias was one of the most amazing institutions of Roman criminal law. It was closely connected to gladiatorial games and this relation caused and influenced its dynamic and complex nature. The goal of this paper is to answer the question about the legal characteristic of damnatio ad bestias, whether it was a kind of death penalty or only a mode of its execution. On the basis of legal sources one can affirm that, at least in the roman jurists’ opinion, damnatio ad bestias was a poena, although sometimes it was omitted in the legal catalogs of penalties used in the field of Roman criminal law. This fact may be reasonably explained by the nature of this punishment – it depended on organization of the games with wild animals, so not everywhere there was appropriate infrastructure and necessary beasts. On the other hand, texts describing this penalty, mostly concerning martyrdom of Christians, may suggest that it was a mere mode of execution. But as it seems, these sources refer to the moment of infliction of damnatio ad bestias and other aggravated forms of death penalty, like burning alive and crucifixion, and to the governors’ jurisdiction. All these three penalties were interchangeable accordingly to the circumstances, which fact may create an idea that they were only forms of execution.